2007
DOI: 10.1007/s00253-007-1024-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-oxygen bond formation by fungal laccases: cross-coupling of 2,5-dihydroxy-N-(2-hydroxyethyl)-benzamide with the solvents water, methanol, and other alcohols

Abstract: Laccase-catalyzed reactions lead to oxidation of the substrate via a cation radical, which has been described to undergo proton addition to form a quinonoid derivative or nucleophilic attack by itself producing homomolecular dimers. In this study, for the substrate 2,5-dihydroxy-N-(2-hydroxyethyl)-benzamide, we show that, besides the quinonoid form of substrate, all products formed are nonhomomolecular ones. Indeed, without addition of a reaction partner, heteromolecular products are formed from the quinonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Together with the redox potential of the T1 site of laccases, which catalyzes the formation of the radical intermediates of the substrates 1a to 1d (Fig. 2, 29), the redox potential difference between the laccase T1 site and the substrate is defined, which in turn determines the reaction velocity. Thus, higher redox potentials of the laccase T1 site and lower redox potentials of the substrate make the redox potential difference larger, resulting in a faster reaction rate 30.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the redox potential of the T1 site of laccases, which catalyzes the formation of the radical intermediates of the substrates 1a to 1d (Fig. 2, 29), the redox potential difference between the laccase T1 site and the substrate is defined, which in turn determines the reaction velocity. Thus, higher redox potentials of the laccase T1 site and lower redox potentials of the substrate make the redox potential difference larger, resulting in a faster reaction rate 30.…”
Section: Resultsmentioning
confidence: 99%
“…With laccase from Bacillus SF spores, it was shown that tyramine and syringylglycerol β‐guaiacyl ether (Scheme C) coupled through a C−O bond because the ortho positions, with respect to the phenyl alcohol, were blocked (Scheme , P1 ) . Further transformations included dehydroxylation ( P2 ), oxidation ( P3 ) and nucleophilic attack by either of the solvents water ( P4 ) or methanol ( P5 ); this has been shown to be rather common in laccase‐mediated oxidation …”
Section: Laccase‐mediated Grafting On Lignocellulosesmentioning
confidence: 99%
“…[39] Further transformations included dehydroxylation (P2), oxidation (P3)a nd nucleophilic attack by either of the solvents water (P4)o rm ethanol (P5); this has been shown to be rathercommon in laccase-mediated oxidation. [40] Apart from grafting phenolics from lignin, Kudanga and coworkers also managed to grafta nd concomitantly hydrophobise beech veneers by using alkylamines. [41] To support their hypothesis that covalent bonding, andn ot mere adsorption,w as responsible for the increase in hydrophobicity,t he authors again reverted back to simple phenolics and lignin model compounds (Scheme 7A,B ).…”
Section: Laccase-mediated Grafting On Lignocelluloses 21 Laccase-mementioning
confidence: 99%
“…Numerous authors have reported that the biological activity of phenolic compounds can be improved modifying phenolic molecules by using the enzyme laccase (EC 1.10.3.2) a polyphenol oxidase 8 . Antioxidant, antitumor, and anti-depressive compounds have been synthesized using this enzyme [8][9][10][11] . Additionally, this enzyme has been recently used for the synthesis of antifungal compounds 12 .…”
Section: Introductionmentioning
confidence: 99%